China's Plan of oriental health preservation technique Ba Duan Jin against the epidemic in the Post-epidemic Era - Jin, Feng; Li, Shiying (The Journal of the International Society of Chinese Health Practices, 2021)
At the beginning of 2020, the novel Coronavirus epidemic broke out and spread rapidly, and a large number of COVID-19 patients were admitted to hospitals for isolation treatment. After more than three months of hard work by the military and civilians across the country, China finally won an initial victory in the fight against COVID-19. In the course of fighting the novel coronavirus, China adopted a combination of Chinese medicine and western medicine according to the characteristics of the Novel coronavirus, and for the first time, included Chinese medicine therapy and an oriental health preservation technique Baduanjin into the treatment plan. In the "COVID-19 patients with hospital rehabilitation program (try out)" and "grassroots health institutions in COVID-19 during the epidemic prevention and control for the elderly patients with chronic diseases to provide medical and health service guide (try out)" notices, the National Health Committee made it clear that eight period of jin shall be used as a rehabilitation treatment of COVID-19 as well as a guide for the treatment of elderly patients with chronic diseases. These notices highlighted the value, mission and responsibility of the Eastern health preservation technique Baduanjin in rehabilitation, strengthening resistance and preventing diseases. COVID-19 has once again demonstrated that the world is a whole, and no country can be an outsider. In the process of this crisis, it has once again highlighted the urgency and importance of building a community with a shared future for mankind. Objective: This study, guided by the "Healthy China 2030" Plan Outline, aims to serve the health of the whole people, implement the health and health work policy of prevention first, deeply explore the value and efficacy of the oriental health preservation technique Baduanjin in the process of fighting the epidemic, and change from treating "already" to preventing "not yet" to move the prevention barrier forward, and contribute China's wisdom and solutions to the global fight against COVID-19. Methods: In this paper, literature review, questionnaire survey, expert interview and other methods were used to systematically analyze the novel Coronavirus concept, clinical type, characterization, patient age trend, psychological characteristics at diagnosis and other aspects. This paper defines the clinical types of the novel coronavirus, the clinical manifestations of COVID-19 patients, the age characteristics of susceptible population, and the psychological dynamics of the public in the face of COVID-19. Results: Through consulting, researching and interviewing senior experts and scholars as well as reviewing the latest experimental results, it is shown that there are different types of COVID-19 in the traditional Chinese medicine and Western medicine. According to the clinical symptoms, medical image analysis, physiological parameters (oxygen saturation, arterial oxygen partial pressure, peripheral blood lymphocytes, peripheral blood inflammatory factors, lactic acid), the Western medicine classifies COVID-19 into xxx. From the perspective of Traditional Chinese medicine, the Novel Coronavirus belongs to the category of epidemic disease. According to the pathogenesis of epidemic disease, it is pointed out that the disease is located in the lung. The basic pathogenesis features are "dampness, heat, poison, and stasis", and the clinical types are: light, normal, severe, critical, and recovery. Through combing a large number of ancient literature, investigation and interview of senior Chinese medicine experts and authority scholars of the oriental health preservation technique Baduanjin, it was found that the oriental health preservation technique Baduanjin has unique functional value for prevention and prognosis recovery of COVID-19. 1) The Oriental health preservation technique Baduanji has a good preventive and recovery effect on the prevention COVID-19 and the recovery of prognostic respiratory function; 2) The combination of body and mind of The Eastern Health preservation technique Baduanjin is helpful to prevent "not sick". The Eastern health preservation technique Baduanjin emphasizes the combination of movement and activity, and the unity of form and spirit, which make the practitioner relax and quiet, eliminate distractions, and pay attention to the coordination of breathing, thoughts and movements, so that the action can reach the meaning. In this way, the mind is quiet and the mood is stable, which can effectively relieve the panic, depression and other emotions caused by the Epidemic; 3) The compatibility between Oriental Health preservation technique Baduanjin and COVID-19 patients. Studies have found that the age structure of COVID-19 patients is mainly middle-aged and elderly, with underlying diseases, who exhibit different degrees of fatigue, anxiety, insomnia and other symptoms. Even if the prognosis is good, most patients have different degrees of respiratory function, physical function, psychological function and other disorders. Dongfang Health maintenance Batuanjin has the functions of removing meridians and dredgers, regulating qi and blood, and regulating the five zang and six fu organs. It is a medium and small intensity aerobic exercise, and has the characteristics of small intensity and slow motion range, which meets the needs of elderly patients with COVID-19, physical weakness and mobility difficulties. Conclusion: Based on the genotype of COVID-19, the pathological characteristics of each period and the unique functions of Oriental health preservation technique Baduanjin, the specific plans are proposed as follows: 1) Moving the anti-epidemic gate forward to the "disease-free" prevention scheme of Oriental health preservation technique Baduanjin; 2) Treatment of "pre-existing disease" by combining physical and medical treatment with Oriental Health preservation technique Baduanjin; 3) Dongfang Health preservation technique Baduanjin helps frontline personnel fight against the Epidemic. Under the background of the new crown outbreak, Oriental body-keeping for shousands of eight brocade in today's society yi is unripe brightness, its governance before disease, during the Epidemic into "disease" to "not" disease prevention, to prevent the reach mark, in the heart of the world's resistance to disease will play an important role, thus contributing the Chinese wisdom and solutions to the mankind and to the global fight against new crown outbreak.